2020
DOI: 10.1021/acs.langmuir.0c02143
|View full text |Cite
|
Sign up to set email alerts
|

Study on Self-Assembled Morphology and Structure Regulation of α-Zein in Ethanol–Water Mixtures

Abstract: α-Zein has received widespread attention owing to its unique solubility, amphipathic, and self-assembly properties, which is because of its high proportion of nonpolar amino acids and unique amino acid sequence. The protein self-assembly is a significant and widely observed phenomenon in many scientific areas such as food and biomedicine, among many industries. In this study, we investigated the self-assembly behavior of α-zein and regulated the morphology and structure of the self-assembled α-zein by varying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 46 publications
1
15
0
3
Order By: Relevance
“…Since different ethanol solutions evaporate faster than water solution, the polarity of the ethanol solution changed quickly as it evaporated, and high ethanol concentrations that present high hydrophobicity may not favor formation of β-sheets structure. Moreover, the morphology and structure of self-assembled α-zein previously revealed antiparallel β-sheets conformation in self-assembling zein nanospheres and nanofibers [ 44 ]. Kim et al [ 45 ] found that the degree of aggregation of zein varied based on the binary solvent mixture’s composition, and as a result, the self-assembly mechanism of zein particles appears to be due not just to their amphiphilic properties, but also to the changing polarity of the solution as it evaporates.…”
Section: Resultsmentioning
confidence: 99%
“…Since different ethanol solutions evaporate faster than water solution, the polarity of the ethanol solution changed quickly as it evaporated, and high ethanol concentrations that present high hydrophobicity may not favor formation of β-sheets structure. Moreover, the morphology and structure of self-assembled α-zein previously revealed antiparallel β-sheets conformation in self-assembling zein nanospheres and nanofibers [ 44 ]. Kim et al [ 45 ] found that the degree of aggregation of zein varied based on the binary solvent mixture’s composition, and as a result, the self-assembly mechanism of zein particles appears to be due not just to their amphiphilic properties, but also to the changing polarity of the solution as it evaporates.…”
Section: Resultsmentioning
confidence: 99%
“…T. Hou et al, 2019;Zeng et al, 2019). One shortcoming of zein is that zein particles are prone to precipitation and aggregation under neutral conditions due to their weak repulsive forces because of the high amount of nonpolar amino acids in the zein molecule (Yu et al, 2020). To improve the stability of the system, water-soluble polysaccharides, such as chitosan, pectin, carrageenan, and gum arabic (GA), are usually involved in forming zein-polysaccharide nanocomposites for better stability (Song et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Esta titulación provoca que el porcentaje de etanol en la mezcla final sea de entre el 10 y 20%, muy inferior a 70-90% de la solución inicial donde esta solubilizada la proteína y el compuesto que se desea encapsular. El segundo método parte de una solución de la prolamina en etanol/agua 70-90%, removiéndose el alcohol mediante evaporación, llegando a concentraciones finales de entre el 5 y 10%, esta técnica es conocida como auto ensamble inducido por evaporación de solvente (EISA) 69,70,71 . La formación de biopelículas se realiza con una metodología similar a la segunda pero generando la evaporación completa del solvente y con concentraciones de α-zeínas de 3 a 4 veces superiores, además de la presencia de algún otro polímero usualmente con propiedades antimicrobianas, que se retícula con la prolamina o genera un proceso de plastificación al interactuar con ella 72 .…”
Section: -Interés Industrial Tecnológico Y Científico En Las Zeínasunclassified
“…Por ejemplo, la facilidad con la que forman oligómeros y agregados, podría relacionarse a su alto contenido en α-hélices en su estructura secundaria, las cuales estarían exponiendo residuos no polares, usualmente involucrados en procesos de agregación proteica 78 . Además, estudios han demostrado que la formación de micro esferas con la prolamina conlleva una ganancia de hebras-β a cambio de pérdidas de α-hélices y giros ricos en glutamina 69,71,77,79 . Es decir esta aplicación se basa en la manipulación de cambios en su estructura secundaria, en un efecto provocado por el aumento de polaridad del solvente.…”
Section: -Importancia De Los Estudios Estructurales En Las α-Zeínasunclassified
See 1 more Smart Citation